Difference between revisions of "009C Sample Midterm 3, Problem 2"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam">For each the following series find the sum, if it converges. If you think it diverges, explain why. ::<span class="exam">(a) (6 points)    &...")
 
 
(5 intermediate revisions by the same user not shown)
Line 1: Line 1:
<span class="exam">For each the following series find the sum, if it converges. If
+
<span class="exam">For each the following series find the sum, if it converges.  
you think it diverges, explain why.
 
  
::<span class="exam">(a) (6 points) &nbsp;&nbsp;&nbsp;&nbsp; <math style="vertical-align: -50%">\frac{1}{2}-\frac{1}{2\cdot3}+\frac{1}{2\cdot3^{2}}-\frac{1}{2\cdot3^{3}}+\frac{1}{2\cdot3^{4}}-\frac{1}{2\cdot3^{5}}+\cdots .</math>  
+
<span class="exam">If you think it diverges, explain why.
 +
 
 +
<span class="exam">(a) &nbsp;<math style="vertical-align: -50%">\frac{1}{2}-\frac{1}{2\cdot3}+\frac{1}{2\cdot3^{2}}-\frac{1}{2\cdot3^{3}}+\frac{1}{2\cdot3^{4}}-\frac{1}{2\cdot3^{5}}+\cdots </math>  
 
<br>
 
<br>
  
::<span class="exam">(b) (6 points) &nbsp;&nbsp;&nbsp;&nbsp; <math style="vertical-align: -75%"> \sum_{n=1}^{\infty}\,\frac{3}{(2n-1)(2n+1)}.</math>
+
<span class="exam">(b) &nbsp;<math style="vertical-align: -75%"> \sum_{n=1}^{\infty}\,\frac{3}{(2n-1)(2n+1)}</math>
 +
<hr>
 +
[[009C Sample Midterm 3, Problem 2 Solution|'''<u>Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
! Foundations: &nbsp;
 
|-
 
|One of the important series to know is the '''Geometric series.''' These are series with a common ratio <math style="vertical-align: 0%">r</math> between adjacent terms which are usually written
 
|-
 
|
 
::<math>\sum_{k=0}^{\infty}a_{0}r^{k}.</math>
 
|-
 
|These are convergent if <math style="vertical-align: -22%">|r|<1</math>, and divergent if <math style="vertical-align: -22%">|r|\geq1</math>. If it is convergent, we can find the sum by the formula
 
|-
 
|
 
::<math>S=\frac{a_{0}}{1-r},</math><br>
 
|-
 
|where <math style="vertical-align: -12%">a_{0}</math> is the first term in the series (if the index starts at <math style="vertical-align: 0%">k=2</math> or <math style="vertical-align: 0%">k=6</math>, then "<math style="vertical-align: -12%">a_{0}</math>" is actually the first term <math style="vertical-align: -12%">a_{2}</math> or <math style="vertical-align: -12%">a_{6}</math>, respectively).
 
|-
 
|Another common type of series to evaluate is a '''telescoping series''', where the telescoping better describes the partial sums, denoted <math style="vertical-align: -15%">S_k</math>.  Most of the time, they are presented as a fraction which requires '''partial fraction decomposition'''.
 
|-
 
|This can be accomplished fairly quickly via a shortcut when the factors in the denominator are linear and share the same coefficient on <math style="vertical-align: 0%">n</math>.
 
|-
 
|'''Example.''' Suppose we wish to decompose the fraction <math style="vertical-align: -30%">\frac{4}{(n-2)(n+1)}</math>.  First, consider the difference
 
|-
 
|
 
::<math>\frac{1}{n-2}-\frac{1}{n-1}</math>
 
|-
 
|If we combine this to a common denominator, we find
 
|-
 
|
 
::<math>\frac{1}{n-2}\cdot\frac{n+1}{n+1}-\frac{1}{n+1}\cdot\frac{n-2}{n-2}\,=\,\frac{n+1-(n-2)}{(n-2)(n+1)}\ =\ \frac{3}{(n-2)(n+1)}.</math>
 
|-
 
|To have a 1 in the numerator, we would just multiply by <math style="vertical-align: 0%">\frac{1}{3},</math> or the reciprocal of the difference between the two constants. Thus
 
|-
 
|
 
::<math>\begin{array}{rcl}
 
{\displaystyle \frac{4}{(n-2)(n+1)}} & = & {\displaystyle 4\cdot\frac{1}{(n-2)(n+1)}}\\
 
\\
 
& = & 4\cdot{\displaystyle \frac{1}{3}\left(\frac{1}{n-2}-\frac{1}{n+1}\right).}
 
\end{array}</math>
 
|-
 
|Notice the pattern: for any fraction of the form<math>\frac{1}{(x+a)(x+b)}</math> where<math>a<b,</math> we have
 
|-
 
|
 
::<math>{\displaystyle \frac{1}{(x+a)(x+b)}\,=\,\frac{1}{b-a}\left(\frac{1}{x+a}-\frac{1}{x+b}\right).}</math>
 
|-
 
|In this manner, we can quickly find that
 
|-
 
|
 
::<math>{\displaystyle \frac{1}{n^{2}-25}\,=\,\frac{1}{(n-5)(n+5)}\,=\,\frac{1}{5-(-5)}\left(\frac{1}{n-5}-\frac{1}{n+5}\right)\,=\,\frac{1}{10}\left(\frac{1}{n-5}-\frac{1}{n+5}\right)}</math>
 
|-
 
|As per the so-called telescoping, consider the series defined by
 
|-
 
|
 
::<math>\sum_{n=2}^{\infty}\frac{1}{n^{2}-1}.</math>
 
|-
 
|Using the technique above, we can rewrite the series as
 
|-
 
|
 
::<math>\sum_{n=2}^{\infty}\frac{1}{(n-1)(n+1)}\,=\,\sum_{n=1}^{\infty}\frac{1}{2}\left(\frac{1}{n-1}-\frac{1}{n+1}\right).</math>
 
|-
 
|This means that
 
|-
 
|
 
::<math>\begin{array}{cclcl}
 
S_{2} & = & \frac{1}{2}\left(\frac{1}{1}-\frac{1}{3}\right)\\
 
S_{3} & = & \frac{1}{2}\left(\frac{1}{1}-\frac{1}{3}+\frac{1}{2}-\frac{1}{4}\right) & = & \frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{3}-\frac{1}{4}\right)\\
 
S_{4} & = & \frac{1}{2}\left(\frac{1}{1}-\frac{1}{3}+\frac{1}{2}-\frac{1}{4}+\frac{1}{3}-\frac{1}{5}\right) & = & \frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{4}-\frac{1}{5}\right)\\
 
S_{5} & = & \frac{1}{2}\left(\frac{1}{1}-\frac{1}{3}+\frac{1}{2}-\frac{1}{4}+\frac{1}{3}-\frac{1}{5}+\frac{1}{4}-\frac{1}{6}\right) & = & \frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{5}-\frac{1}{6}\right)\\
 
\\
 
\vdots & \vdots & \vdots\\
 
S_{n} & = & \frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{n}-\frac{1}{n+1}\right).
 
\end{array}</math>
 
|-
 
|Notice the pattern - each time there are exactly two surviving positive terms, and two surviving negative terms. This is exactly the difference between the two factors in the denominator. If we then take the limit, we find
 
|-
 
|
 
::<math>\sum_{n=2}^{\infty}\frac{1}{n^{2}-1}\,=\,\lim_{n\rightarrow\infty}S_{n}\,=\,\lim_{n\rightarrow\infty}\frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{n}-\frac{1}{n+1}\right)\,=\,\frac{3}{4}.</math>
 
|}
 
  
&nbsp;'''Solution:'''
+
[[009C Sample Midterm 3, Problem 2 Detailed Solution|'''<u>Detailed Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!(a): &nbsp;
 
|-
 
|
 
|}
 
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!(b): &nbsp;
 
|-
 
|
 
|}
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|
 
|}
 
 
[[009C_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009C_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 08:43, 28 November 2017

For each the following series find the sum, if it converges.

If you think it diverges, explain why.

(a)  

(b)  


Solution


Detailed Solution


Return to Sample Exam